Ideologi Bahasa dan Diskursus Identitas dalam Permainan Roleplay Bilingual di Twitter - Fanny Syawbriyanti (Antropologi Indonesia, 2021)
The emergence of new interaction spaces on the internet opened up to the creation of computer-mediated discourse which includes language use in various forms of conversation. This paper describes how discourse developed in role-playing game community on Twitter as a discourse community. Generally, there were three different roleplaying groups based on the use of language: Indonesian, English, and bilingual roleplaying group. This paper focuses on the use of English and Indonesian language among bilingual roleplayers. This language practice was based on language ideologies regarding a dichotomy of ‘in-context’ and ‘out-of-context’ in role-playing game. The use of English was commonly associated with ‘in-context’ situation in which players were entirely immersed into their character. On the contrary, the use of Indonesian language represented ‘out-of-context’ condition in which players detach themselves from their character to express some aspects of their self in real life. However, these opposing poles seemed to merge in the identity construction of bilingual roleplayers as reflected on the ‘decent roleplayer’ discourse. Thus, this paper also explores the relationship between language practice and identity through the way bilingual roleplayers position themselves in interactions.